PENTINGNYA PENGGUNAAN TATA BAHASA DAN EJAAN BAHASA INDONESIA DI SD 14 KOTO BARU PADA KELAS 4 - Rhama Dinda Vanita; Rowin Dayu (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2025)
Abstract: Alphabet and spelling in Grade IV at SD 14 Koto Baru as part of developing scholars' introductory knowledge chops. A solid understanding of proper Alphabet and spelling from an early age is essential for cultivating effective language chops, including reading, memorandum, and speaking. still, the training of ABC constantly faces several challenges. thus, creative training styles that align with the characteristics of abecedarian school scholars are demanded. This exploration uses a descriptive qualitative approach. The data sources in this study are preceptors and scholars. Data collection ways include observation, interviews, and attestation. The data analysis ways applied are data reduction, data donation, and verification. The findings reveal that assignment plans prepared by preceptors serve as a companion for administering effective instruction in the use of proper Alphabet and spelling. The main challenges in using proper ABC include scholars' limited understanding of complex ABC rules, shy training styles, and the strong influence of the scholars’ native or indigenous languages, which hinders their capability to use standard Indonesian rightly. In conclusion, the use of proper Indonesian Alphabet and spelling at SDN 14 Koto Baru has been executed well and plays a vital part in supporting scholars’ language development.